A REVIEW ON COMBUSTION CHARACTERISTICS OF AMMONIA/HYDROGEN/AIR MIXTURES (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
significant attention due to their potential as carbon-free energy carriers. This review synthesizes previous studies on the turbulent flame behavior of these mixtures, focusing on flame speed, stability, ignition delay, and emission profiles. Ammonia, while a promising zero-carbon fuel, exhibits low reactivity and flame speed, which can be enhanced by blending with hydrogen. Hydrogen, known for its high reactivity and diffusivity, significantly improves the combustion performance of ammonia. However, the addition of hydrogen also introduces challenges such as increased NOx emissions and flame instability under certain conditions. Experimental and numerical studies have explored the effects of hydrogen blending ratios, equivalence ratios, and turbulence intensity on flame characteristics. The review highlights the importance of understanding turbulent flame behavior for optimizing the use of ammonia/hydrogen mixtures in practical applications such as power generation, internal combustion engines, and gas turbines.